Active Carbons And Their Reactivation In Non-Ferrous And Noble Hydrometallurgy - V. M. Mukhin (The Minerals, Metals and Materials Society, 2006)
Among the methods proposed for spent activated carbon regeneration, the most acceptable is, thermal reactivation, because in this case the existing equipment for manufacture of activated carbon can be adapted for this purpose. In order to conduct the process of thermal re-activation of spent activated carbon directly at gold mills, a full-scale drum-type furnace with external electric heating has been developed, i.e. EPV-300 model with a throughput rate of 50 to 120 kg/hour. Its use ensures restoration of the adsorption properties of carbon up to the level of fresh activated carbon with an insignificant (by 0.7%) decrease in strength and with a high (95% to 97%) yield of reactivated carbon. During the recent years, activated powder carbon has been extensively used in flotation processes for treating polymetallic ores at ore treating plants to improve recoveries of main metals (copper, lead, nickel, etc.). Especially large volumes of activated powder carbon are used at the Talnakh concentrator of the Norilsk Mining and Metallurgical Complex in Russia for absorption of residual flotation reagents from recycled water in order to ensure efficient selective separation of minerals with similar physical and chemical properties.